Visualisasi Spasial Kunjungan Pasien Rumah Sakit Menggunakan Sistem Informasi Geografis - Rindiyani, Fadillah Dea; Fauzi, Harry; Nadi, Danu Tirta; Hakim, Agya Osadawedya; Aeni, Yomi Nur (Politeknik Negeri Jember, 2025)
Patient visit data at Bandung Paru Hospital is still managed conventionally, without integration with Geographic Information System (GIS) technology. This study aimed to develop and utilize GIS to visualize patient visits, supporting spatial data-based decision-making. A descriptive method was used, with the research population consisting of all patient visits to paru Hospital in 2024. The sample included outpatient and emergency patients selected through purposive sampling. Secondary data were taken from outpatient and emergency visit records, processed, and displayed in thematic maps using color gradients from green to red to indicate visit intensity, from low to high. The results showed that GIS can provide a spatial overview of patient visit distribution, helped identify visit patterns, and supported strategic planning such as improving facilities and services. Paru Hospital is encouraged to adopt GIS for spatial-based visualization of patient visit data, as it allows the data to be presented in interactive maps, offering clearer insights into the geographic distribution of patients.